The Convergence Ball and Error Analysis of the Relaxed Secant Method - Rongfei Lin; Qingbiao Wu; Minhong Chen; Lu Liu (Advances in Mathematical Physics)
A relaxed secant method is proposed. Radius estimate of the convergence ball of the relaxed secant method is attained for the nonlinear equation systems with Lipschitz continuous divided differences of first order. The error estimate is also established with matched convergence order. From the radius and error estimate, the relation between the radius and the speed of convergence is discussed with parameter. At last, some numerical examples are given.